ETFE : Technology and Design - LeCuyer, Annette (Birkhäuser, 2008)
ETFE foil has recently become an important material for the cladding of technologically sophisticated and innovative buildings. This material is very thin and lightweight and, when used in air-filled cushion assemblies, has enormous strength and a range of adaptive environmental attributes. ETFE cushion enclosures became known primarily through Grimshaw Architects’ Eden Project and Herzog + de Meuron’s Allianz Arena, and they are being used on the spectacular swimming stadium for the 2008 Olympic Games in Beijing, the largest ETFE building envelope in the world so far. This book is conceived as an in-depth introduction to the characteristics of ETFE and its applications in construction. Project examples explore in detail the specific characteristics of ETFE building skins in the areas of structural behavior, light transmission, insulation, acoustics, fire engineering and environmental modification.